2022
DOI: 10.1101/2022.09.27.509633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear translocation of spike mRNA and protein is a novel pathogenic feature of SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes severe pathophysiology in vulnerable older populations and appears to be highly pathogenic and more transmissible than SARS-CoV or MERS-CoV. The spike (S) protein appears to be a major pathogenic factor that contributes to the unique pathogenesis of SARS-CoV-2. Although the S protein is a surface transmembrane type 1 glycoprotein, it has been predicted to be translocated into the nucleus due to the novel nuclear localization signal (NLS) "PRRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…In this study, S1 was highly aggregated around and in the nucleus under confocal microscopy (unpublished data). Therefore, we assumed that the potential mechanisms of S1 in the nucleus might be via NPCs, which was recently clarified by Sattar et al 37 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, S1 was highly aggregated around and in the nucleus under confocal microscopy (unpublished data). Therefore, we assumed that the potential mechanisms of S1 in the nucleus might be via NPCs, which was recently clarified by Sattar et al 37 .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we assumed that the potential mechanisms of S1 in the nucleus might be via NPCs, which was recently clarified by Sattar et al . 37 .…”
Section: Discussionmentioning
confidence: 99%
“…• Notably, for CoVs, mRNA transcription is done in a discontinuous manner (Lai, 1996;Rowe et al, 1997), with the viral polymerase functioning in a piecemeal fashion rather than progressing the entire viral genome at once. This fact is well established, as summarized by a recent publication by the NIAID (Sattar et al, 2023): "These coronaviruses contain a positive-strand RNA genome with a few unique features: twothirds of the viral RNA is translated into a large polyprotein, and the remainder of the viral genome is transcribed by a discontinuous transcription process into a nested set of subgenomic mRNAs." • Necessary for the above discontinuous mechanism is that the viral polymerase and nascent RNA transcripts disassociate from the RNA template regularly during RNA transcription, and by necessity then, the CoV polymerase must jump between different RNA molecules during RNA synthesis (Lai, 1996).…”
Section: Feasibility Of Integration Of a Short Stretch Of Synthetic R...mentioning
confidence: 99%
“…In conclusion, there are a myriad of reports about the pathogenic effects of Spike of SARS-CoV-2 (regarding the Spike of the initial variants) in the current literature. One preprint publication on Spike demonstrated that the protein enters the nucleus in human epithelial cells due to presence of a novel nuclear localization signal [ 163 ], which is absent in other coronaviruses. Spike could shuttle mRNA into the nucleus, a phenomenon that could have several implications for the genetic maintenance of cells [ 164 ].…”
Section: Possible Mechanisms Of Covid-19 Mrna Vaccine-induced Tissue/...mentioning
confidence: 99%